Effects of seeding material age, storage time, and tuber tissue zone on glucomannan content of Amorphophallus muelleri Blume (International Journal of Plant Biology, 2018)
Among members of the genus Amorphophallus in Indonesia, Amorphophallus muelleri produces the highest amounts of glucomannan, which is a fiber carbohydrate that plays a significant role in controlling obesity and type 2 diabetes. Glucomannan in A. muelleri is stored in the tubers. Several internal and external factors affect the glucomannan content of the tubers. In this study, we only investigated the internal factors seeding material and tuber. The objectives were: i) to investigate the effect of the seeding material on tuber glucomannan levels; and ii) to assess the influence of the storage period and the tuber part on glucomannan contents. Glucomannan was extracted via centrifugation. The result showed that tubers, which yielded from the center bulbis, have slightly higher glucomannan content than tubers from side bulbis, even though insignificant. Our results indicate significant glucomannan losses at storage times of more than 3 months. Levels decreased by 90% after storage over 3.75 months since shoot collapse. Glucomannan levels of the central and the edge parts of the tubers did not differ significantly.